2020
DOI: 10.3390/biomedicines9010014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Circulating Tumour DNA and Extracellular Vesicle DNA by Low-Pass Whole-Genome Sequencing Reveals Molecular Drivers of Disease in a Breast Cancer Patient

Abstract: There is increasing recognition of circulating tumour DNA (ctDNA) as a non-invasive alternative to tumour tissue for the molecular characterisation and monitoring of disease. Recent evidence suggests that cancer-associated changes can also be detected in the DNA contained within extracellular vesicles (EVs). As yet, there has been limited investigation into the relationship between EV DNA and ctDNA, and no studies have examined the EV DNA of breast cancer patients. The aim of this study was to use low-pass who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…This method has been utilized by some previous studies to clinically identify the cytogenetics [16,17]. In the meantime, circulating Cell-free DNA evaluation by this method has also been reported and thought to be valuable in predicting the prognosis or chemotherapy resistance in non-small cell lung cancer and breast cancer [18][19][20]. Based on these reports, LPWGS is thought to be a reliable method in determine large segments alterations of cancer genomes.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been utilized by some previous studies to clinically identify the cytogenetics [16,17]. In the meantime, circulating Cell-free DNA evaluation by this method has also been reported and thought to be valuable in predicting the prognosis or chemotherapy resistance in non-small cell lung cancer and breast cancer [18][19][20]. Based on these reports, LPWGS is thought to be a reliable method in determine large segments alterations of cancer genomes.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be due to the difference in DNA degradation during storage in FFPE tissue blocks [138,139]. In another study, only one case presented a lower sensitivity to tumor driver CNVs of breast cancer with EV DNA compared with ctDNA [133].…”
Section: Wgs and Wesmentioning
confidence: 95%
“…This technology demonstrated matrix metalloproteases-14 on extracellular vesicles to detect cell invasiveness in vitro ( Zhang et al, 2020 ). However, an investigation into the comparison between extracellular DNA and circulating tumor DNA found that while copy number variants were both detectable in two kinds of DNA, circulating tumor DNA have better sensitivity in serial monitor of BC ( Ruhen et al, 2020 ).…”
Section: Therapeutic Applications Of Exosomes In Breast Cancermentioning
confidence: 99%